Establishing Premium Quality Standards for ‘Monthong’ Durian Using Contest Prize-Winning Characteristics and Public Sensory Evaluation - Prommaneea, Kornkanok; Beckles, Diane M.; Yamane, Hisayo; Siriphanich, Jingtair; Luengwilai, Kietsuda (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
‘Monthong’ is one of the most popular durian cultivars in Thailand and international markets because of its good taste, mild aroma, firm texture, and long shelf life. Premium-grade durians are expensive and in high demand, but clear criteria are still limited. In this study, ‘Monthong’ that won prizes in competitions were selected to examine their characteristics. The common traits found in the winning fruits were considered as potential indicators of premium quality. It was found that all winning durians had a pulp dry matter (DM) content of at least 36%. Moreover, pulp DM also showed a positive correlation with flavor (r = 0.59, P = 0.038). Nevertheless, results from a public sensory test showed that pulp DM ≥36% alone was not enough to define premium quality (χ² = 0.120, P > 0.05). Principal component analysis implied that sweetness, nuttiness, aroma, and low fiber content also influenced consumer preference. When DM ≥36% was combined with these favorable sensory traits, consumers could identify premium durians more accurately. In this case, 76.3% correctly identified premium-quality fruit. These findings suggest that a DM of ≥36% with key sensory traits serves as a reliable criterion for defining the premium quality of ‘Monthong’ durian.